Traditional Uses of the Great Marsh: A Review of Lesser-Known Resources in Massachusetts' Great Salt March. - Holden, Elisabeth; Newman, Janna; Thistle, Ian; Whiteman, Eliza Davenport. (Tufts University. Tisch Library., 2018)
2013 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Eight Towns and the Great Marsh Committee. This project is part of the Office of Sustainability Student Project Database, a place to share and view student projects related to sustainability and the environment.